Pharmacokinetics and pharmacodynamics of intravenous dexmedetomidine in the horse. Issue 1 (28th July 2014) - Rezende, M. L.; Grimsrud, K. N.; Stanley, S. D.; Steffey, E. P.; Mama, K. R.
<x xml:space="preserve">Abstract</x> The aim of the study was to describe the pharmacokinetics and selected pharmacodynamics of intravenous dexmedetomidine in horses. Eight adult horses received 5 μg/kg dexmedetomidine IV. Blood samples were collected before and for 10 h after drug administration to determine dexmedetomidine plasma concentrations. Pharmacokinetic parameters were calculated using noncompartmental analysis. Data from one outlier were excluded from the statistical summary. Behavioral and physiological responses were recorded before and for 6 h after dexmedetomidine administration. Dexmedetomidine concentrations decreased rapidly (elimination half‐life of 8.03 ± 0.84 min). Time of last detection varied from 30 to 60 min. Bradycardia was noted at 4 and 10 min after drug administration (26 ± 8 and 29 ± 8 beats/min respectively). Head height decreased by 70% at 4 and 10 min and gradually returned to baseline. Ability to ambulate was decreased for 60 min following drug administration, and mechanical nociceptive threshold was increased during 30 min. Blood glucose peaked at 30 min (134 ± 24 mg/dL) and borborygmi were decreased for the first hour after dexmedetomidine administration. Dexmedetomidine was quickly eliminated as indicated by the rapid decrease in plasma concentrations. Physiological, behavioral, and analgesic effects observed after dexmedetomidine administration were of short duration.